2021
DOI: 10.1002/aenm.202102058
|View full text |Cite
|
Sign up to set email alerts
|

Natural Lepidolite Enables Fast Polysulfide Redox for High‐Rate Lithium Sulfur Batteries

Abstract: ideally stores five times more energy per mass (1675 mAh g −1 ) than intercalationtype cathodes by multielectron reactions of sulfur, namely S 8 + 16 e − + 16 Li + ⇌ 8 Li 2 S, [8,9] and leads to extensive researches on Li-S batteries.Nevertheless, the development of Li-S batteries is plagued by three issues: (1) the sluggish electrical conductivities of sulfur (σ = 5 × 10 −30 S cm −1 ) and its end products (Li 2 S, σ = 1 × 10 −13 S cm −1 ) lead to slow conversion from soluble lithium polysulfides (LiPSs, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 45 publications
(40 reference statements)
0
48
0
Order By: Relevance
“…Noteworthily, the battery can provide an ultrastable OCV for more than 3000 h with PNAVS, where the PNAGA and PVDF decreased at the very beginning, indicating the great advantage of PNAVS on LiPS adsorption, redox kinetics in Li–S batteries, and promising potential for future practical application and storage. This OCV stability for the battery with PNAVS has already surpassed most of the current reported batteries as shown in Figure b. Dendrite formation is another issue for Li–S batteries. Asymmetrical Li/Cu semicells were employed to evaluate the Coulombic efficiency of different binders on lithium stripping/plating in Figure c.…”
Section: Results and Discussionmentioning
confidence: 85%
“…Noteworthily, the battery can provide an ultrastable OCV for more than 3000 h with PNAVS, where the PNAGA and PVDF decreased at the very beginning, indicating the great advantage of PNAVS on LiPS adsorption, redox kinetics in Li–S batteries, and promising potential for future practical application and storage. This OCV stability for the battery with PNAVS has already surpassed most of the current reported batteries as shown in Figure b. Dendrite formation is another issue for Li–S batteries. Asymmetrical Li/Cu semicells were employed to evaluate the Coulombic efficiency of different binders on lithium stripping/plating in Figure c.…”
Section: Results and Discussionmentioning
confidence: 85%
“…4b), suggesting a more rapid conversion of lithium polysulfides. 42 These electrochemical test results of the symmetrical cells amply proved the catalytic activity of the CoS 2 @montmorillonite composite for the LiPS redox process.…”
Section: Resultsmentioning
confidence: 71%
“…Since the battery was discharged to 1.7 V before the test, peaks at 373, 420, and 570 cm À1 were detected at the beginning of the charging process, which may correspond to S 6 2À + S 8 2À + Li 2 S, S 6 2À , and S 6 2À + Li 2 S 2 + LiS 3 $, respectively. 36,71 When the charging voltage was increased from 1.7 to 2.6 V, it was observed that the signal of S 6 2À was signicantly weakened. The CV curve showed that the oxidation reaction was over (Fig.…”
Section: Resultsmentioning
confidence: 99%